FUNDAMENTALS OF GROWING AGRICULTURAL CROPS IN SALINE SOIL CONDITIONS (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Sufficient measures are being taken to fill the markets of our country with high-quality food products, increase the number of Uzbek fruits and vegetables on world trade routes, as evidenced by the fact that soybeans are grown separately from legumes. paid. The goal is to reduce the mineralization of saline and saline soils, the cultivation of secondary shade in grain-free areas, and meeting the needs of the population through drip irrigation, as well as the preparation of nutritious feed for poultry.